NEW – OLD TRENDS IN THE FIELD OF CRIMINAL POLICY IN THE REPUBLIC OF SERBIA - Đokić, Ivan (Srpska politička misao, 2025)
The Draft Law on Amendments to the Criminal Code of 2025 announces a significant reform of Serbia’s substantive criminal legislation. In addition to a series of newly introduced criminal offences – many of them controversial from a criminal policy standpoint – it also proposes a substantial tightening of sentencing ranges for certain offences. Driven by populist rhetoric and accompanied by an almost dismissive attitude toward the achievements of criminal law scholarship, the Draft disregards empirical knowledge of the real capacities of punishment and the actual effect of increased repression on crime prevention. By threatening excessive penalties for violations of criminal norms in the sphere of serious forms of criminal behavior, the proponent of these measures continues to strengthen retributive tendencies. In doing so, Serbian criminal law increasingly diverges from the liberal, rule-of-law model, and is rapidly transforming into a form of “enemy-oriented” criminal law – one in which all means are considered permissible in the state’s effort to combat threats to the legal order. Such an orientation is inappropriate for a legal system that seeks to preserve democratic features, as it poses a serious risk of undermining fundamental human rights in the realm of punishment. Moreover, it is frequently accompanied by inefficiency and weak results in controlling criminal behavior. It could be said that such an orientation in the field of criminal policy in the Republic of Serbia is nothing new; on the contrary, if we consider the period since the first serious instance of intensified penal repression in 2009 – when the penalty ranges for as many as one third of existing criminal offences were made more severe – the trend toward prescribing increasingly harsher punishments has shown no sign of abating. What is most concerning, however, is the well-founded fear that this tendency has not yet reached its peak and is likely to continue in the future.
Keywords: punishment; repression; life imprisonment; hyper-criminalization; enemy-oriented criminal law